Comparação de qualidade de vida de renais crônicos antes e após o transplante renal e relação entre espiritualidade e qualidade de vida do transplantado renal - Oliveira, Leticia Meazzini de [UNIFESP] (2017)
Introduction: Chronic Kidney Disease (CKD) is a factor for negative health outcomes when associated with major noncommunicable diseases. Survival rate is widely used to evaluate the success of all treatments available for renal replacement, but the patient's perception of his quality of life (QoL) should be valued in all modalities. Objectives: To compare QOL of renal patients when on dialysis and after renal transplantation and to correlate it with sociodemographic variables; morbidities and spirituality/religiosity to QOL of renal transplant patients. Methods: In 2007, we evaluated the QOL of 477 chronic renal patients submitted to hemodialysis (HD) or peritoneal dialysis (PD). After seven years, the QoL of the patients who were part of the initial sample and received the renal transplant were evaluated using the KDQOL-SF instrument; besides these sociodemographic and economic data, spirituality/religiosity information were collected through the WHOQOL-SRPB instrument. Results: Twenty-seven renal transplant recipients were evaluated, out of a total of 63, 15 of whom underwent hemodialysis and 12 underwent peritoneal dialysis. There was a significant improvement in some dimensions of QoL in the post-transplant period and a positive impact of spirituality/religiosity on QoL in some dimensions. Conclusion: Renal transplantation provided improvement in important aspects of QOL in the chronic renal patient, such as: mental composit, effects of kidney disease and burden of kidney disease. Sociodemographic characteristics such as gender, marital status, race, work situation and religion also influenced these indexes. Practices of spirituality / religiosity positively impacted the QoL of renal transplant patients.